Company Loyalty Analysis at PT Legalitas Mudah Indonesia - Cut Aviyanti; Rusdi Musa Ishaq; Prasetyo Hadi (Syntax Corporation Indonesia, 2022)
The sustainability of the company is the goal of every company. To achieve this sustainability, several aspects need to be considered. The synergy between the company's image, customer trust, and reputation in the company can affect customer satisfaction and loyalty. The main objectives of this study are to 1) determine the effect of corporate image on customer satisfaction; 2) determine the effect of customer trust on customer satisfaction; 3) determine the influence of the company's reputation on customer satisfaction, and 4) know the effect of customer satisfaction on customer loyalty. This study uses a quantitative method. This research was conducted at PT. Legalitas Mudah Indonesia. The research sample is a customer of PT. Legalitas Mudah Indonesia amounted to 100 respondents. The instrument used in this research is a questionnaire. Data collection techniques are carried out using observation, interviews, documentation, distribution of questionnaires, and library searches. The results showed that the company's image has a significant positive effect on customer satisfaction. These results are evidenced by the value of t-count 2.742 > t-table 1.986. Customer trust has a significant positive effect on customer satisfaction. These results are evidenced by the value of t-count 3.153 > t-table 1.986. Company reputation has a significant positive effect on customer satisfaction. These results are evidenced by the value of t-count 2.322 > t-table 1.986. Customer satisfaction has a significant positive effect on customer loyalty. These results are evidenced by the value of t-count 3.035 > t-table 1.986.